2015
DOI: 10.1111/rssa.12131
|View full text |Cite
|
Sign up to set email alerts
|

Political Socialization in Flux?: Linking Family Non-Intactness During Childhood to Adult Civic Engagement

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 43 publications
2
17
0
Order By: Relevance
“…Overall, our investigations support the findings from other European studies on the relations between civic and political attitudes and family form (Prokic/Dronkers 2009;Hener et al 2015;Voorpostel/Coffé 2014). Of course, our analysis is just a small step along a long road, but it suggests that parental separation affects more than just the wellbeing of children.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Overall, our investigations support the findings from other European studies on the relations between civic and political attitudes and family form (Prokic/Dronkers 2009;Hener et al 2015;Voorpostel/Coffé 2014). Of course, our analysis is just a small step along a long road, but it suggests that parental separation affects more than just the wellbeing of children.…”
Section: Resultssupporting
confidence: 88%
“…Although the measurement of the family form was very poor in the CivEd 1999 (it did not distinguish between stepparents and biological parents), it found some variation in the societal attitudes of children living in different family forms across different societies. Using longitudinal data from the German Socio-Economic Panel, Hener et al (2015) found a strong relationship between growing up in a "non-intact" family and children's civic, social, and political engagement as adults. They also showed that the duration of time spent in a "non-intact family" as a child has a negative effect on participation as a young adult.…”
Section: Introductionmentioning
confidence: 99%
“…We follow the definition used in the GSOEP study by Hener et al (2016), who define an index of civic engagement as the aggregation of four components: political interest, party identification, organizational involvement and individual voluntarism. Interest in politics and party identification are in general associated with involvement in public matters.…”
mentioning
confidence: 99%
“…whereṘ is the within R-squared from the baseline regression andR is the within Rsquared from the controlled regression. R max is the highest possible R-squared and is set to R max = min(2.2R, 1) following Hener et al (2019). Hence, the movement in coefficients is weighted by the movement in R-squared relative to the potential change in R-squared.…”
Section: Appendix (For Online Publication)mentioning
confidence: 99%